(untitled) (Journal of Asian Development Studies, 2024)
Language disorders are considered a substantial neurodevelopmental disability, within which 7- 10% of children of the global population are affected by different forms of language disorders. These disorders are defined by impairment of language understanding and production, showing lifelong impacts on cognition, learning, communication and social interaction. These questions include: what are the causes of language disorders, how is language disorder diagnosed, and what are the best practices when treating a person with language disorder? This research uses a mixedmethod research design based on theoretical foundations such as the biopsychosocial model, the Neurocognitive Developmental Model by Paula Raja and the Social Interactionism model by Uzer Kaya. A bibliography review was conducted, supplemented by using standardized language tests, neuropsychological examinations, and case reports to study the frequency and cognitive effects of linguistic impairments. These research findings show that language disorders are directly related to severe attention and memory problems, and the structural differences in the brain are identifiable. Furthermore, these disorders come with social and emotional impacts since the patient suffers from anxiety, depression, or poor academic performance. Dynamic assessment and context-based student and context-specific early intervention can effectively reduce these impacts. Applying evidence-based learning across individual learning underscores the need to incorporate cognitive and social factors while teaching language disorders, which is key to the study. This study supports the intervention of multiple disciplines and early detection to improve language and quality of life in affected people.